6. Audio example: Haydn's Symphony no. 100, movement 2 - Haydn, Joseph, 1732-1809 (composer):::Creator::::::::::::; Everett, Nathan (arranger):::Contributor:::::::::::: (2022)
Joseph Haydn's Symphony no. 100 is one of six symphonies that Haydn composed for his second highly successful visit to London in 1794–95. The symphony earned its nickname "The Military" from the second movement, where Haydn introduces a battery of so-called Turkish percussion (triangle, cymbals, and bass drum) as well as real military bugle calls. The movement has a folk-like main theme in a steady march rhythm, with the percussion instruments frequently added for special effect. A stormy contrasting middle section in the minor key is most likely the passage referred to as "the hellish roar of war increased to a climax of horrid sublimity" by a music critic after the symphony's premiere in 1794. The military effects were wildly popular with early audiences, and it is not surprising to find that "Haydn's Military Symphony" (probably referring to the famous second movement) was one of the items in the Panharmonicon's playlist.